Effects of liming on soil biota and related processes in agroecosystems: a review - Priscillar Wenyika; Rebecca Oiza Enesi; Linda Yuya Gorim; Miles Dyck (Discover Soil)
Abstract Soil acidity is associated with nutrient deficiencies and phytotoxicity, and is detrimental to crop productivity due to its effects on plant roots and soil biota. Liming is an effective strategy for managing acidity in agricultural fields. Liming increases soil pH, changing soil chemistry, leading to shifts in community composition and activity of soil biota. However, it is not fully understood how liming impacts different groups of soil biota, their interactions and soil biological health. This review summarizes liming effects on soil biota i.e., plant roots, bacteria, archaea, fungi, nematodes, and earthworms. Reviewed literature indicates that liming increases abundance, diversity and activity of most bacterial species. Liming often increases the abundance of nematodes and earthworms, but some studies showed no liming effects on these communities. Application of lime improves mycorrhizal colonization of plant roots. Liming mostly reduces abundance, biomass and activity of most fungi which tend to favor acidic soils. However, liming effects on fungi were inconsistent; in some studies, liming reduced fungal abundance and the fungal to bacteria ratio, while in other studies, liming showed no impact on both abundance and the ratio. Some variations in liming effects on soil biota were due to differences in duration of liming, liming material used and site-specific environmental characteristics. Overall, this review highlights the complex and variable impacts liming has on soil biota, emphasizing the importance of considering species-specific responses, soil type and environmental conditions when implementing liming strategies. Understanding these dynamics is crucial for optimization of soil health and crop productivity in acidic soils.